Prehospital intravenous epinephrine may boost survival of patients with traumatic cardiac arrest: a retrospective cohort study. Issue 1 (December 2015) - Chiang, Wen-Chu; Chen, Shi-Yi; Ko, Patrick; Hsieh, Ming-Ju; Wang, Hui-Chih; Huang, Edward; Yang, Chih-Wei; Chong, Kah-Meng; Chen, Wei-Ting; Chen, Shey-Ying; Ma, Matthew
Abstract Background Prehospital resuscitation for patients with major trauma emphasizes a load-and-go principle. For traumatic cardiac arrest (TCA) patients, the administration of vasopressors remains under debate. This study evaluated the effectiveness of epinephrine in the prehospital setting for patients with TCA. Methods We conducted a retrospective cohort study using a prospectively collected registry for out-of-hospital cardiac arrest in Taipei. Enrollees were ≥18 years of age with TCA. Patients with signs of obvious death like decapitation or rigor mortis were excluded. Patients were grouped according to prehospital administration, or lack thereof, of epinephrine. Outcomes were sustained (≥2 h) recovery of spontaneous circulation (ROSC) and survival to discharge. A subgroup analysis was performed by stratified total prehospital time. Results From June 1 2010 to May 31 2013, 514 cases were enrolled. Epinephrine was administered in 43 (8.4 %) cases. Among all patients, sustained ROSC and survival to discharge was 101 (19.6 %) and 20 (3.9 %), respectively. The epinephrine group versus the non-epinephrine group had higher sustained ROSC (41.9 % vs. 17.6 %, p < 0.01) and survival to discharge (14.0 % vs. 3.0 %, p < 0.01). The adjusted odds ratios (ORs) of epinephrine effect were 2.24 (95 % confidence interval (CI) 1.05-4.81) on sustained ROSC, and 2.94 (95 % CI 0.85-10.15) on survival to discharge. Subgroup analysis showed increased ORs of epinephrine effect on sustained ROSC with a longer prehospital time. Conclusion Among adult patients with TCA in an Asian metropolitan area, administration of epinephrine in the prehospital setting was associated with increased short-term survival, especially for those with a longer prehospital time.